THE INFLUENCE OF WORK MOTIVATION, COMPENSATION, AND WORK DISCIPLINEON EMPLOYEE PERFORMANCE AT PT INDAH PONTJAN Kab. SERDANG BEDAGAI (Case Study of Harvesters) - Redika Pasaribu; Hidayati Purnama Lubis; Wilchan Robain (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research was conducted at PT. Indah Pontjan with the aim of analyzing the influence of work motivation, compensation and work discipline partially and simultaneously on employee performance. The population is 500 employees who work in the company, the sample is a harvest workforce of 200 people by random sampling using the Slovin formula to obtain a research sample of 67 people. The types of data used are primary and secondary data, data collection techniques using questionnaires, literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption testing and hypothesis testing.The research results show that: 1) work motivation partially has a positive and significant effect on employee performance at PT. Indah Pontjan District. Serdang Bedagai with (tcount>ttable value, 6.118 > 1.667 at sig. 0.000 <0.05) so that the research hypothesis H1 is accepted. 2) Compensation partially has a positive and significant effect on employee performance with (tcount>ttable value, 2.653 > 1.667 at sig. 0.011 <0.05). 3). Work discipline partially has a positive and significant effect on employee performance with (tcount>ttable value, 2.419 > 1.667 at sig. 0.020 <0.05). It can be concluded that work motivation, compensation and work discipline partially and simultaneously have a positive and significant effect on employee performance. There is a strong correlation between work motivation, compensation and work discipline with employee performance, a percentage of 36.6% and the remaining 63.4% can be explained by other variables not studied such as incentives, promotions and so on.